PENGARUH LATIHAN SIRKUIT TERHADAP DAYA TAHAN PADA TIM SEPAKBOLA SMKN 5 PEKANBARU - Ilham Ashari; Ramadi '; Kristi August (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this study came from the interim results of observation carried out by researchers in the field. Researchers found the problem is the lack of durability that is owned by the football team SMKN 5 Pekanbaru. The purpose of this study was to determine the effect on the endurance circuit training on the football team SMKN 5 Pekanbaru. The study used the approach of one-group pretest-posttest design. The population in this study is a soccer player who SMKN Pekanbaru 5 of 16 people by using total sampling where all population sampled, to obtain research data using preliminary tests pretest and post-test after it was given a circuit workout. Diproleh The data were analyzed using t-test. Based on data analysis found that a circuit workout effect on durability on the football team SMKN 5 Pekanbaru, marked from the results diproleh namely 2,595 tcount > rtable 1,753. From the results obtainable circuit training effect on the durability of the soccer team SMKN 5 Pekanbaru.Keywords: Circuit training, endurance